Eliminating violence against children: Hanbook for parliamentarians N° 13 - 2007 (2007)
This handbook is designed to promote active and effective follow-up by Parliaments and parliamentarians throughout the world to the recommendations of the United Nations Secretary- General’s Study on Violence against Children. This handbook uses, with permission, text from the report of the UN Secretary- General’s Study to the General Assembly and from the complementary World Report on Violence against Children